Osseointegration programmatic development: interdisciplinary team with a patient-centered approach - Amber Stanley, BSPH; Meghan K. Wally, PhD; Christine Churchill, MA; Kristine McGuire, LCSW; Tarey Strickland, PT, DPT, ATC; Angela Abernethy, PT, MPT, CBIS; Toby Perkins, CTR; Angelica M. Melendez, BS; Kevin Hickey, PA-C; Rachel B. Seymour, PhD; Joseph R. Hsu, MD (OTA International)
Abstract. Successful implementation of an osseointegration program requires a skilled and committed interdisciplinary team engaged in supporting patients and their families throughout the OI process. The roles and responsibilities of clinical and ancillary team members are described in detail, along with a discussion of the needed patient and family support resources. Time spent developing the interdisciplinary team, with strong regulatory support and engagement of hospital administration and the health system, will promote higher patient satisfaction and outcomes and innovative future directions.